Borderless empire : Dutch Guiana in the Atlantic world (1750-1800) - Hoonhout, Bram (Early American places., 2020)
"BORDERLESS EMPIRE explores the volatile history of Dutch Guiana, in particular the forgotten colonies of Essequibo and Demerara, in order to provide new perspectives on European empire building in the Atlantic world. It argues that imperial expansion was a process of improvisation at the colonial level, rather than a project that was centrally orchestrated from the metropolis. Furthermore, it emphasizes that colonial expansion was far more transnational than the oft-used divisions into "national Atlantics" suggest. It therefore aims to transcend the framework of the "Dutch Atlantic" by looking at the connections across cultural and imperial boundaries. This book tells a story of empire building as an Atlantic-wide process. Essequibo and Demerara remained remarkably open colonies, even as late as the end of the eighteenth century. But that is not to say they were unique: improvisation, and the consequent contacts across imperial borders were a general feature of early modern colonial ventures. By looking outwards from the colonies, rather than following the top-down view from the metropolis, BORDERLESS EMPIRE aims to bring these entanglements to the fore. Highlighting the contribution of many non-Dutch actors--such as Amerindian soldiers, North American provisions traders, and British slave smugglers--it reveals the truly Atlantic nature of empire building. BORDERLESS EMPIRE makes an important contribution to the study of early modern imperialism, Atlantic history, and the historiography of "--